BAHAN DAN CARA PEMBUATAN ARCA BATU SEBAGAI KOMPONEN PENTING CANDI-CANDI MASA KLASIK DI JAWA - Hari Lelono (Balai Arkeologi Yogyakarta, 2013)
Most of the building of temples Hindu / Buddhist in Java, always equipped with statues as a symbol of the manifestation of the gods. These statues are usually placed in the temple chambers in accordance with their respective functions. One thing that is interesting about how to obtain the materials and manufacturing process performed by the artists sculpture carving during the Ancient Java era?. Therefore, the approach tries to uncover ethno-archaeology through ethnographic data. From these data, expected to be useful for science as well as add insight for anyone who wants to know about the 'secret' making of the statues in the Java-Kuna. Our ancestors have proven that they have the genius of local identity and identity as a cultural and civilized nation.